TQM and Product Innovation: Are these Influential Factors of Competitive Advantage? An Empirical Evidence - Osman, Abu Rashed; Hoque, Shah Md Safiul; Ashraf, Mohammad Ali (Journal of Ecohumanism, 2024)
This study examines the impact of TQM and product innovation on competitive advantage. Correlation coefficient and regression analysis are used to examine the relationship between TQM, product innovation, and competitive advantage. The study is followed by a quantitative approach, and the sample of the study is drawn from the manufacturing and service industries located in the Sohar city of Oman. A total of 131 samples was analyzed to judge the hypotheses. The empirical results of this study confirm that TQM and product innovation are both significantly correlated to competitive advantage. Thus, to remain competitive in the marketplace, the management of organizations should give high priority to these influential factors. This empirical study is considered the first study investigating the impact of TQM and product innovation on competitive advantage, adding great value to existing literature from the perspective of Oman.